A Systematic Review of Minimally Invasive Procedures for Mesial Temporal Lobe Epilepsy: Too Minimal, Too Fast?. Issue 2 (16th April 2021) - Wang, Ryan; Beg, Usman; Padmanaban, Varun; Abel, Taylor J; Lipsman, Nir; Ibrahim, George M; Mansouri, Alireza
Abstract: BACKGROUND: Cortico-amygdalohippocampectomy (CAH) is effective for mesial temporal lobe epilepsy (mTLE). Concerns regarding surgical morbidity have generated enthusiasm for more minimally invasive interventions. A careful analysis of current data is warranted before widespread adoption of these techniques. OBJECTIVE: To systematically review the use of laser interstitial thermal therapy (LITT), stereotactic radiosurgery (SRS), radiofrequency thermocoagulation (RF-TC), and focused ultrasound for mTLE. METHODS: Major online databases were searched for prospective observational studies, randomized clinical trials, and retrospective studies (>50 patients), including mTLE patients. Outcomes of interest were seizure freedom (Engel I), complications and re-operation rates, and neuropsychological and quality-of-life (QoL) data. RESULTS: Nineteen publications were identified. At ≥6 mo postoperatively, LITT (9/19) Engel I outcomes ranged from 52% to 80%. SRS (3/19) has a latency period (52%-67%, 24-36 mo postoperatively) and the radiosurgery vs. open surgery for epilepsy (ROSE) trial reported inferiority of SRS compared to CAH. RF-TC (7/19) demonstrated variable seizure freedom rates (0%-79%) and high re-operation rates (0%-90%). Twelve studies reported neuropsychological outcomes but QoL (4/19) was not widely reported, and few studies (3/19) assessed both. Study quality ranged from fair to good. CONCLUSION: Based on nonrandomized data, LITT has compelling evidence of efficacy; however, comparisons to surgical resection are lacking. SRS has a latency period and is inferior to CAH (ROSE trial). RF-TC is a less resource-intensive alternative to LITT; however, comparisons of efficacy are limited. Additional studies are needed before minimally invasive procedures can supplant standard surgery.